THE INFLUENCE OF SOCIAL MEDIA MARKETING, TOURISM FACILITIES AND CUSTOMER SATISFACTION ON THE INTEREST OF RE-VISITING TOURISTS IN MEPAR CAMPING TAKENGON - Wahda Tunisa; Jullimursyida; Chalirafi; M. Subhan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to determine the influence of social media marketing, tourist facilities, customer satisfaction on the interest in returning tourists to Mepar camping Takengon. The population in this study were tourists who visited Mepar Camping Takengon. The data for this research uses a questionnaire as a data collection instrument. This research uses a quantitative approach using the statistical tool SPSS (Statistical Package For The Social Sciences). The number of samples used in this research was 100 respondents and the sampling technique in this research used the lemeshow formula. The analysis used is the multiple linear regression test and coefficient of determination, while the hypothesis test uses the T test. The results of this study show that partially social media marketing has a positive and significant effect on interest in repeat visits, tourism facilities partially have a negative and insignificant effect on Interest in repeat visits and customer satisfaction partially have a positive and significant effect on interest in repeat visits. The Adjusted R Square value is 45.7% while the remaining 54.3% can be explained by other variables not examined in this study.